Fuel cell and hydrogen technologies research, development and demonstration activities in Singapore – An update. (24th August 2016) - Chan, Siew Hwa; Stempien, Jan Pawel; Ding, Ovi Lian; Su, Pei-Chen; Ho, Hiang Kwee
Abstract: In this paper the authors review the activities of Singapore-based research institutions and business players in the field of fuel cells and associated hydrogen technologies undertaken till date. The scope of this paper spans almost 15 years of accomplishments and focuses on highlighting the acquired capabilities and achievements. The review shows slow, but consistently growing research activities, demonstration undertakings and business endeavours of local and overseas companies. Highlights: Complete history of hydrogen and fuel cells RD&D activities in Singapore. Contributions from research institutions, business and demonstrations. Consistent buildup of capacity in hydrogen technologies happens in Singapore.